Politicas de los GADS Municipales para el acogimiento de los adultos mayores para garantizar los derechos constitucionales de las personas - Torres Alvarez, Angela Vanessa (2015)
Elder Rights are constitutionally recognized, however inefficient state shown in the full implementation of benefits to seniors. The violation of the rights of the elderly is a harmful and destructive behavior; against their physical, psychological, sexual economy, autonomy, finance, rights and privileges conferred to the group, this situation is worrying and novel because impact in the fields: political, social, health and economic. Worldwide, the rate of abuse in developed countries is high, in countries like Mexico, Argentina, Chile and Peru was the thirty-six percent. Abuse of the elderly; is regarded worldwide as a phenomenon of social, little recognized and underestimated in every sense, and although not precisely established its causes, poor research shows that a high percentage of abuse especially intra-level family. The aim of the research presented is to establish a standard of the Organic Code of Territorial Autonomy and Decentralization Organization for the implementation of programs to ensure the constitutional rights of persons older. To determine the importance of the issue we conducted field research and interviews with polls that allowed us to strengthen the proposed solution to the problem.